Socio-Spatial Relationship between Pesantren and The Local Community: Case Study Darul Ulum Islamic Boarding School in Jombang - Muhammad, Amjad; Setiawan, Bakti; Hidayati, Isti (Jurnal Planologi, 2025)
Since its establishment in 1885, Darul Ulum (PPDU) Jombang Islamic Boarding School has a long history of having a socio-spatial relations with the local community. Utilizing a qualitative analysis of in-depth interview with PPDU’s management and the local community, this research found that the socio-spatial relations is reflected in the forms of familiarity and bounded solidarity. These are formed through face-to-face interactions and reciprocal relationships that provide mutual benefits. From a spatial perspective, this relationship occurs due to distance and boundaries. These findings are interesting because there remains only few research on “pesantrens” that focuses on their socio-spatial relations with the local community from the perspective of urban and regional planning.Keywords: Pondok Pesantren, Socio-Spatial Relation, Familiarity, Bounded Solidarity, Local Community